Purkinje cell degeneration, a new neurological mutation in the mouse. - Mullen, R J (1976)
A new autosomal recessive mouse mutation, Purkinje cell degeneration (pcd), is described. Mutants exhibit a moderate ataxia beginning at 3 to 4 weeks of age. The ataxia results from postnatal degeneration of virtually all cerebellar Purkinje cells beginning around 15 to 18 days of age and progressing rapidly over the next 2 weeks. In addition to the cerebellar disease there is slow progressive degeneration in the retina (photoreceptor cells) and olfactory bulb. Also, adult males have abnormal sperm.